2018
DOI: 10.1111/spsr.12333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Issue‐Specific Political Advertisements in the 2015 Parliamentary Elections of Switzerland

Abstract: Our paper captures the influence of political advertisements on vote intentions in the framework of the 2015 parliamentary elections. We focus on the two winning parties, the FDP and SVP, and the promotion of their stances on immigration/asylum, relations to the EU and the economy. We make use of an extensive database on political advertisements collected in 50 important national and regional newspapers that we link to the Selects respondents. Our findings only hint at limited effects of issue-specific adverti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Similarly, the current results are in line with Tresch and Feddersen’s (2019) findings that media coverage tended to stabilize competence perceptions. The results also support evidence brought by Zumofen and Gerber (2018) . Advertisements during the campaign could “boost” the competence perceptions of a party, although they found rather small effects, which may be due to differences in the design.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Similarly, the current results are in line with Tresch and Feddersen’s (2019) findings that media coverage tended to stabilize competence perceptions. The results also support evidence brought by Zumofen and Gerber (2018) . Advertisements during the campaign could “boost” the competence perceptions of a party, although they found rather small effects, which may be due to differences in the design.…”
Section: Resultssupporting
confidence: 83%
“…Using RCS panel data on the 2015 Swiss elections, Tresch and Feddersen (2019) found that competence perceptions are more unstable and sensitive to media coverage than the associative dimension. Relying on the same data as the previous authors, Zumofen and Gerber (2018) studied the effects of issue-specific advertisements on voting intentions and competence perceptions. They showed that advertisements during the campaign could “boost” the competence perceptions of a party, even though the effects were rather small.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Other contributions link the Selects data with external data sources. To study the impact of the election campaign on vote intentions, Zumofen and Gerber ( 2018 ) make use of an additional dataset on political advertisements collected by the Année Politique Suisse (APS) at the University of Bern and link it to the panel/rolling cross‐section survey. Lutz et al.…”
Section: Methodological Innovations In the Study Of Swiss Electoral Rmentioning
confidence: 99%